Opportunities and Entrepreneurship - Eckhardt, Jonathan T.; Shane, Scott A. (Journal of Management, 2003)
This article extends and elaborates the perspective on entrepreneurship articulated by Shane and Venkataraman (2000) and Venkataraman (1997) by explaining in more detail the role of opportunities in the entrepreneurial process. In particular, the article explains the importance of examining entrepreneurship through a disequilibrium framework that focuses on the characteristics and existence of entrepreneurial opportunities. In addition, the article describes several typologies of opportunities and their implications for understanding entrepreneurship.